Combating plagiarism in the classroom / Wong Soon Heng - Wong, Soon Heng; Ho, Chui Chui (Universiti Teknologi MARA, Kedah, 2011)
As plagiarism is a perennial problem among university students, there is a wealth of literature on this issue. In this paper, the authors share some of the practices they have adopted to combat the plagiarism problem such as teaching paraphrasing and referencing skills, requiring multiple drafts and authenticity statements. Feedback from students has shown that they find these practices useful to help them use sources ethically.